2010
DOI: 10.1002/adfm.201001054
|View full text |Cite
|
Sign up to set email alerts
|

Anchoring Hydrous RuO2 on Graphene Sheets for High‐Performance Electrochemical Capacitors

Abstract: Hydrous ruthenium oxide (RuO2)/graphene sheet composites (ROGSCs) with different loadings of Ru are prepared by combining sol–gel and low‐temperature annealing processes. The graphene sheets (GSs) are well‐separated by fine RuO2 particles (5–20 nm) and, simultaneously, the RuO2 particles are anchored by the richly oxygen‐containing functional groups of reduced, chemically exfoliated GSs onto their surface. Benefits from the combined advantages of GSs and RuO2 in such a unique structure are that the ROGSC‐based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
691
4
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,168 publications
(705 citation statements)
references
References 49 publications
9
691
4
1
Order By: Relevance
“…For pure ruthenium dioxide, the specific capacitance was 705.6 F/g whereas fore activated carbon a value of 119.3 F/g was obtained. A ruthenium oxide/graphene sheet composite was prepared in [88]. The fine RuO 2 particles with a size of 5-20 nm separate the graphene sheets.…”
Section: Metal Oxides and Their Compositesmentioning
confidence: 99%
“…For pure ruthenium dioxide, the specific capacitance was 705.6 F/g whereas fore activated carbon a value of 119.3 F/g was obtained. A ruthenium oxide/graphene sheet composite was prepared in [88]. The fine RuO 2 particles with a size of 5-20 nm separate the graphene sheets.…”
Section: Metal Oxides and Their Compositesmentioning
confidence: 99%
“…[25][26][27][28] It has been reported that the use of MOsN and GO nanocomposites may result in improved biosensor efficacy compared to when a single component is used. [29][30][31][32][33] Recently, a GO and titanium oxide (TiO 2 ) nanocomposite has been explored for the development of lithium ion batteries, photocatalysts and dye sensitized solar cells. 34 However, the RGO and MOsN composite have not yet been used for the fabrication of an electrochemical immunosensor.…”
Section: Introductionmentioning
confidence: 99%
“…The pseudocapacitor undergoes reversible redox reaction that occurs in the electrode materials, such as metal oxides (RuO 2 , MnO 2 , Co 3 O 4 , NiCo 2 O 4 , CoMoO 4 , etc.) [7][8][9][10][11][12][13][14][15][16] and metal hydroxides (Co(OH) 2 , Ni(OH) 2 , etc. ); [17][18][19] it stores more charges and provides higher specific capacitance than does the EDLC.…”
mentioning
confidence: 99%